Learning Strategies in the 21st Century: Opportunities and Challenges - Novita Barokah; Lulut Suhermi; Rahmat Kamal (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
Education in the 21st century requires teachers as educators to be more adaptive and innovative in developing critical, creative, communicative, and collaborative thinking skills. However, not all teachers are able to play such a role. Therefore, metasa researchers need to re-actualize literacy about learning strategies in the 21st century. The purpose of this study is to re-strengthen the actualization of the concept of learning strategies in responding to challenges in the 21st century. This research method uses Systematic Literature Review (SLR), this study analyzes various scientific sources related to learning strategies that are in accordance with the needs of modern education. The results of this study indicate that there are several learning strategies that can be actualized by teachers in responding to the challenges of education in the 21st century, including examining the definition of learning strategies in the contexy of 21st century education, identifying criteria for selecting relevant strategies, types of 21st century learning strategies, opportunities utilized in implementing learning strategies and challenges that need to be overcome by educators. These findings are expected to be a reference for educationin developing learning strategies that are in accordance with the demands of the times.